1999
DOI: 10.1175/1520-0477(1999)080<0271:tmcida>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Man computer Interactive Data Access System: 25 Years of Interactive Processing

Abstract: On 12 October 1998, it was the 25th anniversary of the Man computer Interactive Data Access System (McIDAS). On that date in 1973, McIDAS was first used operationally by scientists as a tool for data analysis. Over the last 25 years, McIDAS has undergone numerous architectural changes in an effort to keep pace with changing technology. In its early years, significant technological breakthroughs were required to achieve the functionality needed by atmospheric scientists. Today McIDAS is challenged by new Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 3 publications
0
37
0
Order By: Relevance
“…Though the spatial resolution of GOES-12 is 4 km at nadir, the actual resolution over the CONUS ranges from 4.7 km over southeast Florida to 8.9 km along the U.S.-Canada border in eastern Montana. The GOES data were acquired from the University of Wisconsin-Madison's Space Science and Engineering Data Center (UW-SSEC) via the Man computer Interactive Data Access System (McIDAS-X; Lazzara et al 1999). …”
Section: Data a Goes-12mentioning
confidence: 99%
“…Though the spatial resolution of GOES-12 is 4 km at nadir, the actual resolution over the CONUS ranges from 4.7 km over southeast Florida to 8.9 km along the U.S.-Canada border in eastern Montana. The GOES data were acquired from the University of Wisconsin-Madison's Space Science and Engineering Data Center (UW-SSEC) via the Man computer Interactive Data Access System (McIDAS-X; Lazzara et al 1999). …”
Section: Data a Goes-12mentioning
confidence: 99%
“…The 1-km image data were normalized and destriped to reduce the effect of detector noise and variability. Two to four 5-min granules from each orbit were remapped into a polar stereographic projection at 2-km resolution and composited with the Man computer Interactive Data Access System (McIDAS; [11]). The resulting images are 2800 2800 pixels in size.…”
Section: Applicationmentioning
confidence: 99%
“…Visible imagery were archived hourly between 1315 and 2215 UTC, while the 10.7-m imagery were archived hourly between 0015 and 2315 UTC. Image processing and analysis were done on personal computers with the Man computer Interactive Data and Analysis System (McIDAS) software (Lazzara et al 1999). McIDAS is the software backbone for the Regional and Mesoscale Meteorology Advanced Meteorological Satellite Demonstration and Interpretation System (Molenar et al 2000), which has been demonstrated at several National Weather Service (NWS) offices.…”
Section: Data Collection and Preparationmentioning
confidence: 99%